Polska debata polityczna wobec eurokonstytucji - Lesiewicz, Elżbieta (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2009)
In the analysis of different attitudes of Polish political groups towards the European Union and the Constitutional Treaty one needs to take into account historical context as well as the political one. It is a spontaneous approach in Poland to think about the Poles in terms of a nation rather than in tzenship. The collapse of communism was followed by an eruption of national feeling, yet many Poles also wanted Poland to open itsEurope. The opportunity to gainss the European Union was, i enst for Poles. The opponents of the EU are fuelled by the sh historical experience of losing our identity. They represent the so-called closed orientation, in which one defends one’ ways while being very distrustful towards the EU. By contrast, an open orientation strives for collaation, seeks cooperation and is trustful European integration. This is reflected in lish political arena.